Św. Ambroży w literaturze, kulcie i zwyczajach polskich - Maria Kunowska-Porębna (Vox Patrum, 1998)
Saint Ambrosius is a well-known personage in Poland, both in national culture and in folklore. The works of the saint were used in sermons at the beginning of sixteenth century by Jan from Szamotuły, Hieronim Powodowski and Stanisław Sokołowski. St. Ambrosius thoughts influenced Kalwin, Nikolau Rej and Jakub Wujek SJ. He was quoted by preachers in the baroque period and in nineteenth century.